Utilization of Content Management System for Web Design Fastly and Creatively at Komenwa "Mahasurya" Jawa Timur (Nusantara Science and Technology Proceedings, 2021)
Each member of the command of the student regiment in the Komenwa "Mahasurya" Jawa Timur is expected to have basic abilities related to physical, mental, and intellectual. Nowadays, Komenwa personnel also need to adapt to the digital era that has penetrated almost all aspects of our lives. One of the skills needed is the skill to create web applications, which will later be able to support Komenwa in developing web independently to spread the vision and mission, organizational public relations functions, and coordination of all Komenwa personnel spread across various regions of East Java. Through this community service activity, we propose a CMS (Content Management System) technology transfer for fast and creative web design at the Komenwa "Mahasurya" Jawa Timur. This CMS is a "shortcut" that is practically used for the general public to be able to create websites quickly and creatively. The training activity was held on August 18, 2021, with 20 participants from Komenwa, located in the laboratory of the Informatics Department, Faculty of Computer Science, UPN "Veteran" Jawa Timur. The participants not only understood the presentation from the presenters but also directly practiced on the computer in the laboratory which had been adapted to meet the needs of this activity. The participants were very enthusiastic about participating in this activity because it was a new thing for them, which gave them added value to their understanding and skills. Through this program, it is hoped that the members of Komenwa "Mahasurya" Jawa Timur will have the ability to design their own web according to their own creativity. So that later Komenwa “Mahasurya” Jawa Timur will have the independence to present themselves in the world wide web or online portals.